1996
DOI: 10.1002/(sici)1099-0720(199602)10:1<85::aid-acp372>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of confabulation to the memory, intelligence, suggestibility and personality of prison inmates

Abstract: This study investigates the relationship of confabulation to memory, intelligence, suggestibility and personality, as measured by the Eysenck Personality Questionnaire and the Gough Socialisation Scale. The subjects were 255 Icelandic prison inmates. Confabulation was measured from the memory narrative of the Gudjonsson Suggestibility Scale (GSS 1). The two components of confabulation—distortions and fabrications—were scored and analysed separately. Distortions and fabrications correlated poorly with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Normative data collected by Gudjonsson (1997a) show that confabulatory responding during GSS free recall is a phenomenon with a relatively low base rate in the normal population. There are also indications that this GSS parameter is considerably more dicult to measure compared to the Yield and Shift parameters (Gudjonsson & Sigurdsson, 1996;Smith & Gudjonsson, 1995). The current study relied on a relatively small and non-clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Normative data collected by Gudjonsson (1997a) show that confabulatory responding during GSS free recall is a phenomenon with a relatively low base rate in the normal population. There are also indications that this GSS parameter is considerably more dicult to measure compared to the Yield and Shift parameters (Gudjonsson & Sigurdsson, 1996;Smith & Gudjonsson, 1995). The current study relied on a relatively small and non-clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Milne et al (1999) reported that cognitively impaired young adults recalled more confabulated details (especially of the Person type) than non-impaired participants. However, Milne et al (1999) suggested that this observation could have reflected the use of poor questioning techniques by one interviewer (i.e., suggestive, forced-choice questions) and individual differences among participants (e.g., differences in personality; Gudjonsson & Clare, 1995;Gudjonsson & Sigurdsson, 1996).…”
mentioning
confidence: 99%
“…The mean scores and standard deviations for both the juvenile and adult samples for the Yield 1, Yield 2, Shift, and Total GSS 1 scores are provided in Table . These are listed alongside the results from normative data for court referrals of Gudjonsson and Sigurdsson (), which consisted of 234 individuals from Britain referred for judicial purposes, typically involving pretrial assessments, and normative data from 100 alleged false confessors from the United Kingdom (Gudjonsson, ). In addition, normative data for juvenile offenders of Sigurdsson and Gudjonsson (), which consisted of 108 Icelandic juvenile offenders who had pleaded guilty to criminal offenses, almost exclusively property offenses, and had been given a conditional discharge, are listed.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the comparison of the U.S. Forensic sample with the Gudjonsson British adult court referrals (Gudjonsson & Sigurdsson, ), Gudjonsson Icelandic juvenile offenders (Sigurdsson & Gudjonsson, ), Gudjonsson British adolescent offenders residing in a secure unit (Richardson et al, ), and Gudjonsson British adult alleged false confessors or retracted confessors (Gudjonsson, ). As can be seen, although Yield 1 for the British adult court referral sample is similar to the U.S.…”
Section: Discussionmentioning
confidence: 99%